2015
DOI: 10.1021/acs.jafc.5b01509
|View full text |Cite
|
Sign up to set email alerts
|

Excretory, Secretory, and Tissue Residues after Label and Extra-label Administration of Flunixin Meglumine to Saline- or Lipopolysaccharide-Exposed Dairy Cows

Abstract: Twenty lactating dairy cattle were intravenously infused with either lipopolysaccharide (LPS) (n = 10) or sterile saline (n = 10). Five cattle in each group received three doses of flunixin meglumine administered by either intravenous infusion or intramuscular injection at 24 h intervals. Milk, urine, and tissues were collected. Thirty-six hours after the last flunixin administration, milk from six cows contained 5-hydroxyflunixin (5OHF) levels greater than the milk tolerance of 2 ng/mL; by 48 h, milk from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 27 publications
3
55
1
Order By: Relevance
“…Numerous studies have shown that disease alters the pharmacokinetics of various drugs2101531. The degree of pharmacokinetic changes depends on the severity of the disease.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that disease alters the pharmacokinetics of various drugs2101531. The degree of pharmacokinetic changes depends on the severity of the disease.…”
Section: Methodsmentioning
confidence: 99%
“…administration, the C 0 was determined to be 11.9 μg/ml and the C max was 5.50 μg/ml after i.m. administration in adult Holsteins (Smith et al., ).…”
Section: Summary Of Pharmacokinetic Parameters For Adult Holstein Cowmentioning
confidence: 99%
“…In that study, flunixin was detected in the highest concentrations of eight compounds measured by gas chromatography–mass spectrometry (Barker, 2008). No studies report the presence or threat of flunixin from cattle manure despite that flunixin regularly exceeds residue levels in meat and milk of cattle (Leavens et al, 2014; Smith et al, 2015). Dairy cows accounted for 59% of flunixin violations in 2014 (USDA‐FSIS‐OPHS, 2015), with multiple studies finding that cattle are still excreting flunixin in their milk at concentrations above the regulatory limit after a 36‐h holding period (Kissell et al, 2013; Smith et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…No studies report the presence or threat of flunixin from cattle manure despite that flunixin regularly exceeds residue levels in meat and milk of cattle (Leavens et al, 2014; Smith et al, 2015). Dairy cows accounted for 59% of flunixin violations in 2014 (USDA‐FSIS‐OPHS, 2015), with multiple studies finding that cattle are still excreting flunixin in their milk at concentrations above the regulatory limit after a 36‐h holding period (Kissell et al, 2013; Smith et al, 2015). Additionally, the metabolite 5‐hydroxyflunixin is excreted for longer periods of time than its parent molecule in milk (Smith et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation